Differential cerebrovascular risks in glioblastoma and meningioma patients: a population-based matched cohort study in Wales (United Kingdom). (15th October 2021) - Poon, Michael T C; Jin, Kai; Brennan, Paul M; Figueroa, Jonine; Sudlow, Cathie
Abstract: Aims: There is limited evidence on cerebrovascular risks in glioblastoma and meningioma patients. We aimed to compare cerebrovascular risks of these patients with the general population. Method: We used population-based routine healthcare and administrative data linkage in this matched cohort study. Cases were adult glioblastoma and meningioma patients diagnosed in Wales 2000-2014 identified in the cancer registry. Controls from cancer-free general population were matched to cases (5:1 ratio) on age (±5 years), sex and GP practice. Factors included in multivariable models were age, sex, index of multiple deprivation, hypertension, diabetes, high cholesterol, history of cardiovascular disease, and medications for cardiovascular diseases. Outcomes were fatal and non-fatal haemorrhagic and ischaemic stroke. We used flexible parametric models adjusting for confounders to calculate the hazard ratios (HR). Results: Final analytic population was 16, 921 participants, of which 1, 340 had glioblastoma and 1, 498 had meningioma. The median follow-up time was 0.5 year for glioblastoma patients, 4.9 years for meningioma patients, and 6.6 years for controls. The number of haemorrhage and ischaemic stroke was 154 and 374 in the glioblastoma matched cohort, respectively, and 180 and 569 in the meningioma matched cohort, respectively. The adjusted HRs for haemorrhagic and ischaemic stroke were 3.74 (95%CI 1.87-6.57) and 5.62 (95%CI 2.56-10.42) in glioblastoma patients, respectively, and were 2.42 (95%CI 1.58-3.52) and 1.86 (95%CI 1.54-2.23) in meningioma patients compared with their controls. Conclusion: Glioblastoma and meningioma patients had higher cerebrovascular risks; these risks were even higher for glioblastoma patients. Further assessment of these potentially modifiable risks may improve survivorship.